2008
DOI: 10.1016/j.compositesa.2007.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Mixed mode I + II interlaminar fracture of carbon/epoxy laminates

Abstract: Abstract. This paper describes a study of the mixed mode I + II fracture of carbon/epoxy unidirectional and multidirectional specimens with symmetric, quasi-symmetric and markedly asymmetric legs. A beam model was developed for predicting the compliance and total strain energy release rate, G. Model predictions agreed well with three-dimensional finite element results for double cantilever beam, end-notched flexure and mixed mode bending tests. The mode mix was evaluated from a virtual crack closure technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 32 publications
(34 reference statements)
0
39
2
Order By: Relevance
“…In spite of mode-I and mode-III, crack front distribution in mode-II was uniform with the exception of localized peaks at the specimen edge [36,37] and crack advance was linear and no difference was detected between crack length at the edges and in the center of the specimen. This point demonstrated that, in mode-III as mode-I loading, there was a higher potential for the growth of crack in the center width of adhesive pad, which indicated that a crack can grow in mode-I and mode-III without being noticed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of mode-I and mode-III, crack front distribution in mode-II was uniform with the exception of localized peaks at the specimen edge [36,37] and crack advance was linear and no difference was detected between crack length at the edges and in the center of the specimen. This point demonstrated that, in mode-III as mode-I loading, there was a higher potential for the growth of crack in the center width of adhesive pad, which indicated that a crack can grow in mode-I and mode-III without being noticed.…”
Section: Resultsmentioning
confidence: 99%
“…However, the plateau size presenting the amount of mode-III component remained sensibly at the same level, meaning that distribution of strain energy release rates could not explain the crack length dependence of G IIIc . Similarly, crack front in mode-I showed such a behavior in adhesive joints and composite materials such as SERR had the maximum and minimum values in the middle width of adhesive layer and at edges, respectively; leaving the edges, SERR increased and approached a constant value (plateau region) and decreased while getting closer to the edges [34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 11 illustrates the temperature dependence of fracture toughness calculated using the experiment results (average values) and Eq. (13). Fracture toughness is almost constant from 23 to 90°C.…”
Section: Temperature Dependencementioning
confidence: 85%
“…The flexural strength using Eq. (12) together with a= 0.5 mm and G C ¼ 600J=m 2 [8,13] is depicted in Fig. 10.…”
Section: Verification Of the Modelmentioning
confidence: 99%
“…On the one hand, the starter crack length should be close to 70% of the half-span ( Fig. 1) in order to avoid a fast, often unstable, propagation in high mode II set-ups [12,16,26]. On the other hand, spurious loading pin compression effects occur when the long fracture process zone caused by the mode II component approaches half-span.…”
Section: Introductionmentioning
confidence: 96%